Proceso de atención de enfermería aplicado a paciente en embarazo de 12 semanas de gestación más hiperémesis gravídica. - Zapata Garofalo, Ariana Lisbeth (2021)
Pregnancy is a process that makes changes in the body, which the pregnant woman must constantly adapt, reacting to the first symptoms that appear in pregnancy. In the following clinical study we describe a 12-week pregnant patient with hyperemesis gravidica, who presents with nausea and vomiting in an alarming amount, causing risk to the fetus and herself as mild malnutrition and threatened abortion, the objective of This clinical case is the application of the nursing care process in a pregnant woman with hyperemsis gravidica, where the problems demonstrated by the patient were identified, it was established that the etiology of hyperemesis gravidica does not appear as such, so this is a symptom normal in the presence of a pregnancy, a treatment was decided to control these symptoms and avoid future complications. The care plan that was established was analyzed and the nursing diagnoses were prioritized, which were related to the patient's health status, in turn, it was linked to the interventions that allowed to provide specific care to the patient, improving her clinical picture. We conclude that a necessary intervention and adequate treatment effectively transformed the evolution of the state of health of the pregnant woman and the fetus.